The Coral Fish in the Coastal Areas, Likupang Kampung Ambong Village, East Likupang District, North Minahasa Regency - Ari B. Rondonuwu; Ruddy Dj. Moningkey; John L. Tombokan (Sam Ratulangi University, 2019)
The aims of this study, 1). To find out the number of species and the abundance of coral fishes; 2). To find out the biomasssa of target fish in carnivorous and herbivorous groups. Data collection was carried out at 5 meters depth using the Underwater Visual Census (UVC) method. The area observation is 150 m2. Coralivorous fish are found with 8 species and are categorized as medium. 28 species of target fish were found from carnivorous fish (13 species), and herbivorous fish (15 species). For total individual number that is 81 individuals and a density that is 3240 individuals/Ha. The highest number of individuals is found in herbivorous fish. The high value of the ecological index shows the stability of the community and the ability of the environment that allows species of fish to grow and develop in their habitat. The target fish is generally in the class size of 16-20 cm and 21-25 cm. In general, reef fish from the group of herbivores are most commonly found in this location.Keywords: Coral Fishes, Likupang Kampung Ambong ABSTRAK Tujuan penelitian, yaitu 1). Untuk mengetahui jumlah spesies dan kelimpahan individu ikan karang; 2). Untuk mengetahui biomasssa ikan target kelompok karnivora dan herbivora. Pengambilan data dilakukan pada kedalaman 5 meter dengan metode Underwater Visual Census (UVC). Luas areal pengamatan adalah 150 m2. Ikan koralivora yang ditemukan berjumlah 8 spesies dan dikategorikan sedang. Ditemukan 28 jenis ikan target dari ikan karnivora (13 spesies), dan ikan herbivora (15 spesies). Untuk kelimpahan individu total yaitu 81 individu dan densitas 3240 individu/Ha. Jumlah individu tertinggi ditemukan pada ikan herbivora. Tingginya nilai indeks ekologi menunjukkan kemantapan komunitas dan kemampuan lingkungan yang memungkinkan jenis-jenis ikan untuk bertahan dan berkembang pada habitatnya. Ikan target umumnya pada kelas ukuran 16 - 20 cm dan 21 – 25 cm. Pada umumnya ikan karang dari kelompok herbivora yang paling banyak ditemukan di lokasi ini. Kata Kunci: Ikan Karang, Likupang Kampung Ambong, Biomassa